Escamas de peixe Corvina (Micropogonias furnieri) reticuladas com glutaraldeído : estudo cinético e termodinâmico da interação com Cd(II) por calorimetria isotérmica - Silva, Esdras Santos (2012)
The present work describes the synthesis of an adsorbent material and its application for the removing of Cd(II) from aqueous solutions. The adsorbent was synthesized by the reaction of scales of Corvina fish (Micropogonias furnieri) in acidic aqueous buffered solutions of glutaraldehyde (GA), with the advantages of its simplicity, inexpensive costs and high thermal decomposition resistance. The characterizations of the materials were performed before and after chemical GA modification and after the adsorption of Cd(II), using diffuse reflectance spectroscopy, FTIR, Raman spectroscopy, SEM, spectroscopy of dispersive energy X-ray diffraction, TG/DTG and DSC thermal analyses and determination of the point of zero charge. The adsorption kinetics of Cd(II) on the adsorbent at 25˚C has shown that the chemical equilibrium of Cd(II) adsorption was reached after 300 min of contact time. The maximum Cd(II) adsorbed was equal to 2.22 x 10-5 g mol-1 and is comparable with Cd(II) sorption values cited in literature using other biosorbents. The kinetic parameters using isothermal calorimetry has shown that a variable-kinetic-order model was most significant in the description of sorption of Cd (II) features. The thermodynamic study showed that the values the adsorptions enthalpies increases with increasing temperature and decreases with increasing concentration of the metal ion. The adsorbent was stable and highly effective to adsorb Cd(II) from aqueous solutions.